2015
DOI: 10.18097/pbmc20156103332
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling in the pathogenesis of neuro-oncology diseases

Abstract: The review summarizes current knowledge on the Hedgehog signaling pathway, its role in normal embryogenesis and/or initiation and progression of neuro-oncological diseases, especially of high-grade gliomas, the most malignant neuroepithelial tumors. The main proteins forming the Hedgehog signaling pathway include Shh, PTCH1, SMO, HHIP, SUFU and GLI1 isoforms. Effects of other signaling pathways on the family of transcription factors GLI and other proteins are described. The review summarizes modern data about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 92 publications
(204 reference statements)
0
1
0
Order By: Relevance
“…37 Some other scientists have reported that in gliomas Hedgehog signaling pathway is activated abnormally. SMO and Gli1 are recognized as positive markers of Hedgehog signaling pathway, and Sufu as a negative marker.…”
Section: Discussionmentioning
confidence: 99%
“…37 Some other scientists have reported that in gliomas Hedgehog signaling pathway is activated abnormally. SMO and Gli1 are recognized as positive markers of Hedgehog signaling pathway, and Sufu as a negative marker.…”
Section: Discussionmentioning
confidence: 99%